Research on sound fields generated by laser-induced liquid breakdown - Hui, Cao; Limin, Gao (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
The sound field excited by laser-induced liquid breakdown is studied through theory and experiment by using fundamental theories of acoustics. It is shown that there is a logarithmic linear relationship between the photoacoustic signals produced by a pulsed laser in liquid and the laser energy. Using the continuity of photoacoustic signals in liquids, a method is obtained to compute the breakdown threshold in liquids, when the distance between the observation point and the laser-induced breakdown area is much longer than cylinder length. The acoustic pressure amplitude is inversely proportional to the distance but proportional to the length of laser-induced breakdown. The acoustic pulse signal amplitude becomes largest in the direction perpendicular to the spreading direction of light. The acoustic pulse signal amplitude becomes smallest if parallel to the direction of light.
Optica Applicata, Vol. 40, 2010, nr 4, s. 897-907
Keywords: optyka; photoacoustic effect; optical breakdown; radiated sound pressure; plasma column